PENERAPAN PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS IV SDN TAMBAKROMO 2 NGAWI - Fahmi, Muhammad Nahdi (Universitas Nusantara PGRI Kediri, 2017)
Abstract: Researchers found some problems in the process of learning grade IV SDN Tambakromo 2 Ngawi, among others: (1) as 5 children out of 20 students who are active in the following study with good results, or by 25%, the number of children it is the students who are willing and dare to ask or propose. (2) as many as 15 children in the medium category and are very passive in the following study or by 75%. (3) as many as 8 children from 20 children or 60% daily test results are still below minimum completeness criteria. In carrying out the study. This study was conducted on May 07, 2016 until May 22, 2016. This study presents the result of observation activity and learning outcomes obtained from the observation score and evaluation in every cycle. In cycle I, average of student’s activity reached 70,45%. While the learning outcomes reached 73,2 with the total number of 11 students who succeeded. In cycle II, the average of students’ activity was 88,64%. While the learning outcomes reached 81,2 with the total number of 17 students who succeeded. In cycle III, the improvement of average students’ activity was 97,73%. While the learning outcomes reached 85,7 with the total number of 19 students who succeeded from 20 the number of students. This proves that the using a scientific approach can improve the fourth grade students learning outcomes IPS at SDN Tambakromo 2 Ngawi. Keywords: Scientific Approach, Social Science Learning, Activity and Social Science Learning Outcomes